Evaluasi Pelayanan Administrasi Kecamatan Mojoroto Kota Berdasarkan Indeks Kepuasan Masyarakat 2024 - Dyah Ayu Rahmawati; Djoko Susanto; Mashuri Mashuri (Universitas 17 Agustus 1945 Semarang, 2025)
This study aims to evaluate the performance of administrative services in Mojoroto District, Kediri City based on the 2024 Public Satisfaction Index (IKM) Survey. Based on the survey results, all performance indicators showed very good results, with an aggregate IKM score reaching 93.12. The assessment of service quality includes employee competence, infrastructure, and service innovations such as online systems and mobile services. In addition, the timeliness of administrative processing, service effectiveness, and employee independence and work commitment were also recorded as optimal. The public gave a positive assessment of administrative services, exceeding their expectations according to the Expectancy Disconfirmation Theory (Oliver, 1980). However, there are obstacles such as disruptions to the information system, fluctuations in requests, and lack of document readiness from the public. This study contributes to improving the quality of public services, with recommendations for strengthening the IT system, managing fluctuations in requests, and increasing public awareness of the required documents. These findings are expected to be a model for effective and responsive public administration services for other sub-districts in Kediri City.